2018
DOI: 10.1093/toxsci/kfy266
|View full text |Cite
|
Sign up to set email alerts
|

Teratological and Behavioral Screening of the National Toxicology Program 91-Compound Library in Zebrafish (Danio rerio)

Abstract: To screen the tens of thousands of chemicals for which no toxicity data currently exists, it is necessary to move from in vivo rodent models to alternative models, such as zebrafish. Here, we used dechorionated Tropical 5D wild-type zebrafish embryos to screen a 91-compound library provided by the National Toxicology Program (NTP) for developmental toxicity. This library contained 86 unique chemicals that included negative controls, flame retardants, polycyclic aromatic hydrocarbons (PAHs), drugs, industrial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…Godfrey et al (2017) found no significant alterations in locomotor activity in zebrafish larva exposed to 13 µL TBBPA. Similarly, an absence of behavioral changes in zebrafish embryos or larvae exposed to TBBPA was reported by several other investigators (Noyes et al 2015;Dach et al 2019;Jarema et al 2015;Truong et al 2014). In contrast, Chen et al (2016) found that zebrafish embryos exposure to 5 µM TBBPA altered larval behavior as evidenced by diminished activity bursts, lower speed of movement, motor deficits, delayed cranial motor neuron development, and inhibited primary motor neuron development.…”
Section: Zebrafishsupporting
confidence: 62%
“…Godfrey et al (2017) found no significant alterations in locomotor activity in zebrafish larva exposed to 13 µL TBBPA. Similarly, an absence of behavioral changes in zebrafish embryos or larvae exposed to TBBPA was reported by several other investigators (Noyes et al 2015;Dach et al 2019;Jarema et al 2015;Truong et al 2014). In contrast, Chen et al (2016) found that zebrafish embryos exposure to 5 µM TBBPA altered larval behavior as evidenced by diminished activity bursts, lower speed of movement, motor deficits, delayed cranial motor neuron development, and inhibited primary motor neuron development.…”
Section: Zebrafishsupporting
confidence: 62%
“…Finally, we compared the morphological effects of ibogaine, IBG, and TBG using a well-established zebrafish developmental toxicity assay. 24 Ibogaine (100 μM) significantly increased malformations and mortality at 2 and 5 days post-fertilization (dpf), respectively ( Fig. 2d – e ).…”
Section: Tbg Is a Safer Non-hallucinogenic 5-ht2a Agonistmentioning
confidence: 92%
“…In this study, we use zebrafish, a well-established model for assessing teratology and developmental neurotoxicity (Dach et al, 2018;Hagstrom et al, 2018;Noyes et al, 2015, Levin andCerutti 2009). Embryos/larvae were exposed to 0.024, 0.12, 0.6 mg/L (0.08, 0.4, 2 μM) THC, 0.006, 0.03, 0.15 mg/L (0.02, 0.1, 0.5 μM) CBD, or 0.05% DMSO control.…”
Section: Introductionmentioning
confidence: 99%